Análise de viabilidade econômica do mercado de microgeração fotovoltaica on grid no Estado do Maranhão - MORAES FILHO, José Ribamar Santos (2017)
Competitiveness and innovation are constants which must be measured for the business success in the business world. In the last years, the costs of electric energy represent the significant increase in the budget of companies and the residential consumers, having them to search for the optimization of costs, in order to produce more or less. Attached to such conceptions, the photovoltaic residential solar energy offers many advantages to those who want to invest in this sector, which can be highlighted: to be the source of clean energy, minimize the environmental impacts, reducing the price of power bill and other factors. In this context, the work presents an economic viability analysis in the market of photovoltaic microregion on grid in the State of Maranhao, working as a source of research to new entrepreneurs who want to be inserted in the photovoltaic sector as the ones who are in the process of consolidation. The indicators of economic viability were the payback, Current Liquid Value (CLV), Return Internal Tax (RIT) and the Profitability Rate (PR), applied to the data of energy generating of cities in the State of Maranhao. From such analysis, it was proven that it is viable to invest in the photovoltaic sector in the State both by the analyzed indicators of viability and by the environmental viewpoint, presenting favorable natural characteristics to such investment.